EFEKTIVITAS BUNGA TELANG (CLITORIA TERNATEA) TERHADAP RESPON GLIKEMIK: SISTEMATIK REVIEW: EFFECTIVNESS OF BUTTERFLY PEA FLOWER (CLITORIA TERNATEA) ON GLICHEMIC RESPONS: SYSTEMATIC REVIEW - Nadhira, Raisa; Natasya, Anita; Hendrawati, Anjani; Audyta, Rindi; Octaviani, Tiara; Nurul Aini, Yasinta; Heri Ridwan; Diding Kelana Setiadi (Politeknik Insan Husada Surakarta, 2024)
Background: Diabetes mellitus is a chronic disease that is globally prevalent and has reached a very high prevalence rate. In 2021, more than 422 million people worldwide will suffer from diabetes. Various databases have reported that one of the ornamental plants, namely the butterfly pea flower (Clitoria Ternatea), has quite a hypoglycemic effect. Purpose: The aim of this systematic research is to help in understanding the potential of butterfly pea flowers as an antidiabetic agent. Methods: The research method we used in this systematic review search was the PRISMA method. This article searches literature sources in Pubmed and Google Scholar databases from 2013 to 2023 using appropriate inclusion criteria. Clitoria Ternatea has excellent anti-diabetic properties. Result: In vitro analysis showed that water extract of butterfly pea flower (Clitoria Ternatea), ethanol extract, and protein extract effectively inhibited the Î±-amylase enzyme, hemoglobin glycosylation, and AGE formation. They also show increased glucose absorption. Conclusion: This explains that CTE can suppress postprandial glucose and insulin responses induced by sucrose through inhibiting intestinal sucrose. It can be concluded that butterfly pea flowers (Clitoria Ternatea) are effective against glycemic responses in the body.